Peningkatan Kapasitas SDM Wirausaha Pemula dan Mitra Universitas Andalas - Prima Fithri; Livia Sara Putri; Amri Syahardi; Puti Afra Zenri Utami; Yola Octaviani Asri (Warta Pengabdian Andalas, 2019)
In a business, human resources are very much needed to be the drivers of various kinds of businesses that will be carried out by employees. Employees have different levels of work in carrying out their skills, but sometimes employees don't even know what to do related to the amount of work they have to do. For this reason, training and development for human resources were needed so that employees can understand their work so that what is the goal of a business can be quickly implemented and achieve the expected targets. Training and development for human resources was an activity to increase the capacity of human resources to become good quality resources in terms of knowledge, work skills, a high level of professionalism in working to improve the ability to achieve company goals properly. For this reason, Andalas University conducted training to improve the ability of human resources as well as what is needed to support the smooth running of the business for beginner entrepreneurs and partners of Andalas University. One of the trainings was to preparing business players to be able to legalize their business. This training was very much needed so that the HR of business actors pay more attention to their businesses, especially in terms of legality. The training was expected that business operators, especially tenants and Andalas University partners, have business legality.